UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN DARUJU (Acanthus ilicifolius L.) DENGAN METODE PEREDAMAN RADIKAL BEBAS 1,1-DIPHENYIL-2-PICRYLHIDRAZIL (DPPH) - Selpida Handayani; Ahmad Najib; Nurul Purnama Wati (Faculty of Pharmacy, Universitas Muslim Indonesia, 2018)
Sea holly leaves (Acanthus ilicifolius L.) belongs to Acanthaceae family, contain flavonoid compounds, alkaloids, an phenols. This research aimed to determine the antioxidant activity of sea holly leaf extract by free radical damping method 1,1-Diphenyl-2-Picrylhydrazil (DPPH). The extraction method multilevel maseration using n-hexane extract, ethyl acetate extract, and ethanol extract is 1,55%, 0,65% and 4,97% respectively. On each extract, the antioxidant activity was assayed by DPPH free radical inhibition method by measuring is absorbance at the maximum wavelength of 515nm using UV-VIS spectrophometer with quercetin compound as comparator. The result of antioxidant assay showed that IC50 value, ethanol extract is 34,659 μg/mL (strong antioxidant), ethyl acetate extract is 162,512 μg/mL (weak antioxidant), n-hexane extract is361,730 μg/mL (not active as antioxidant).